2021
DOI: 10.1056/nejmoa2114228
|View full text |Cite
|
Sign up to set email alerts
|

Waning Immunity after the BNT162b2 Vaccine in Israel

Abstract: Background In December 2020, Israel began a mass vaccination campaign against coronavirus disease 2019 (Covid-19) by administering the BNT162b2 vaccine, which led to a sharp curtailing of the outbreak. After a period with almost no cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, a resurgent Covid-19 outbreak began in mid-June 2021. Possible reasons for the resurgence were reduced vaccine effectiveness against the delta (B.1.617.2) variant and waning immunity. The e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
878
4
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 1,003 publications
(964 citation statements)
references
References 16 publications
71
878
4
11
Order By: Relevance
“…We read with interest the article by Dimeglio et al 1 , showing the importance of the SARS-CoV-2 anti-S antibody response. Along with previous results showing a strong decrease of antibody and neutralization titers after vaccination 2,3 , especially for Gamma variant, their results highlight the usefulness of assessing antibody levels among HealthCare Workers (HCWs) and to monitor the effects of emerging SARS-CoV-2 variants. Likewise, the article by Douxfils et al 4 , demonstrated post-vaccination decreasing neutralizing antibodies titers and highlighted the difficulty to obtain a definite protection threshold., They also could not verified the effects of Alpha and Delta variants.…”
Section: Dear Editorsupporting
confidence: 65%
See 1 more Smart Citation
“…We read with interest the article by Dimeglio et al 1 , showing the importance of the SARS-CoV-2 anti-S antibody response. Along with previous results showing a strong decrease of antibody and neutralization titers after vaccination 2,3 , especially for Gamma variant, their results highlight the usefulness of assessing antibody levels among HealthCare Workers (HCWs) and to monitor the effects of emerging SARS-CoV-2 variants. Likewise, the article by Douxfils et al 4 , demonstrated post-vaccination decreasing neutralizing antibodies titers and highlighted the difficulty to obtain a definite protection threshold., They also could not verified the effects of Alpha and Delta variants.…”
Section: Dear Editorsupporting
confidence: 65%
“…Likewise, the article by Douxfils et al 4 , demonstrated post-vaccination decreasing neutralizing antibodies titers and highlighted the difficulty to obtain a definite protection threshold., They also could not verified the effects of Alpha and Delta variants. Recently, Goldberg et al 3 assessed Delta breakthrough infections among a large vaccinated population and demonstrated a decreasing protection in all age groups a few months after receiving a full vaccination scheme. To date, little data are still available regarding comparative neutralizing capability of antibodies against Alpha and Delta variants several months after vaccination schemes.…”
Section: Dear Editormentioning
confidence: 99%
“…Reasons could be multifaceted, from ever-changing/mutating virus, the waning of vaccine efficacy, and daily medications for other co-morbid conditions, including autoimmune diseases. Multiple studies in USA and Israel have shown that vaccine efficacy decreases over time [3][4][5][6]. Breakthrough COVID infections match the timing of about six months after the first group of high-risk workers and the elderly were vaccinated against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 98%
“…Though this study did not study the waning of vaccine efficacy, further research on this possibility is warranted as both mRNA vaccines were very effective against COVID early after vaccine administration, and effectiveness reduced significantly with time. It is essential to note an early study from Israel that did study the rate of infection in patients who previously received two doses of the Pfizer-BioNTech vaccine for SARS-CoV-2: immunity waned in all age groups [4]. This case report showcases fully vaccinated patients who were hospitalized for severe COVID-19.…”
Section: Introductionmentioning
confidence: 90%
“…3 Despite the efficacy of COVID-19 vaccines is now straightforward and unquestionable, even higher than that of vaccines used for preventing other respiratory infectious diseases such as Influenza, 4 waning immunity against SARS-CoV-2 has been widely reported, especially 4 to 6 months after completing the primary COVID-19 vaccination cycle, 5 so that there is ongoing debate as to whether additional vaccine booster doses may be necessary to restore the immune response to levels similar to or even greater than those achievable immediately after completing a primary COVID-19 vaccination. 5 This article is hence aimed at providing an updated analysis of primary COVID-19 vaccination and vaccine booster doses efficacy by analyzing data emerging from the ongoing Italian nationwide COVID-19 vaccination campaign.…”
Section: Introductionmentioning
confidence: 99%